Remote vs. In-person Delivery of LearningRx One-on-One Cognitive Training During the COVID-19 Pandemic: A Non-inferiority Study - Moore, Amy Lawson; Miller, Terissa Michele; Ledbetter, Christina (Frontiers in Psychology, 2021)
The COVID-19 pandemic challenged in-person delivery of cognitive training. Some clinics pivoted to remote delivery for those impacted by lockdowns, illness, or fear of exposure to the virus. However, it was unknown if remote delivery using teleconferencing technology was as effective as in-person delivery. The current study compared the outcomes of remote delivery to in-person delivery of ThinkRx cognitive training during 2020. The sample included 381 child and adult clients from 18 cognitive training centers. One group (n = 178, mean age = 12.3) received traditional in-person delivery of cognitive training. The second group (n = 203, mean age = 11.7) received remote delivery of one-on-one cognitive training via Zoom teleconferencing. Each client was assessed before and after the intervention using the Woodcock Johnson IV Tests of Cognitive Abilities. Clients completed an average of 112 hours of cognitive training delivered by a clinician in 90- minute sessions 3 or 4 days per week. Paired samples t tests revealed significant differences from pretest to post-test across all constructs for both groups. After Bonferroni correction, MANOVA revealed no significant difference in changes scores between the two intervention groups on any of the subtests. With very small effect sizes, linear regression analyses indicated that age was a significant predictor of change in working memory and processing speed for the in-person group, and a significant predictor of change in overall IQ score for the teletherapy group. Noninferiority analyses indicated remote delivery is not inferior to in-person delivery on the primary outcome measure of overall IQ score along with processing speed, fluid reasoning, long-term memory, and visual processing. Although in-person training results were slightly higher than remote training results, the current study reveals remote delivery of cognitive training during COVID-19 was a viable alternative to in-person delivery of cognitive training with little practical differences based on the age of client.